Analysis Working Relationship Between Employees and Notaries/PPAT (Study at the Khairul Anwar Nasution Notary Office) - Yeltriana Yeltriana; Ismed Coal (Rechtsnormen: Journal of Law, 2025)
Background. This research is based on the complexity of the employment relationship between employees and Notaries/PPATs, particularly regarding rights and obligations, forms of employment agreements, and legal certainty, which often give rise to ambiguity and potential conflicts. Purpose. The main objective of the research is to analyze the characteristics of the employment relationship at the Khairul Anwar Nasution Notary Office, assess the level of compliance of these work practices with applicable employment regulations, and identify obstacles and alternative solutions in implementing equitable employment relationships. Method. This research uses an empirical juridical approach with a descriptive-qualitative method; primary data were collected through interviews with employees and Notaries/PPATs, direct observation, and review of employment agreement documents, while secondary data were obtained from legal literature, employment regulations, and relevant court decisions. Results. The results show that the employment relationship at the office is generally characterized by a subordination relationship, with employment agreements often not set out in writing, and there is uncertainty regarding the length of employment, fulfillment of wage rights, social security, and legal protection. Conclusion. In conclusion, although there is awareness regarding the importance of compliance with employment regulations, employment practices at the Khairul Anwar Nasution Notary Office are not yet fully in line with legal provisions, so it is necessary to prepare written.